2004
DOI: 10.1159/000078489
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Cephalalgia

Abstract: We report a patient with cardiac cephalalgia and review reported cases from the English-language literature based on the new diagnostic criteria published in the International Classification of Headache Disorders, ed 2. Twenty-two patients, including ours, with headaches of cardiac origin were reviewed. The cases fit three of the four new criteria well: Criteria B (acute myocardial ischemia has occurred, 100%), C (headache developed concomitantly with acute myocardial ischemia, 100%), and D (headache resolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…Throbbing and pressing pain were the most frequently reported in previous case reports (8) whereas an observational study found that throbbing quality was the most common (33.3%) (7). Contrary to previous case reports, that in most cases described severe headache (57.9%) (813), we found that in one-half of patients the intensity was moderate.…”
Section: Discussioncontrasting
confidence: 99%
“…Throbbing and pressing pain were the most frequently reported in previous case reports (8) whereas an observational study found that throbbing quality was the most common (33.3%) (7). Contrary to previous case reports, that in most cases described severe headache (57.9%) (813), we found that in one-half of patients the intensity was moderate.…”
Section: Discussioncontrasting
confidence: 99%
“…III, aVF NA Not performed Morlote, 2002 [ 37 ] M/59 Hyperlipidemia, Hypertension Chest discomfort, diaphoresis. NA ST depression NA NA Source Sex/Age Risk Factors Symptoms of Cardiac ischemia Cardiac Enzyme ECG Stress Test DSA Sathirapanya, 2004 [ 38 ] M/58 Smoking Chest tightness NA ST elevation in V1-3 NA LM 50% stenosis, LAD occlusion, 1st OM 70% stenosis, RCX occlusion Chen, 2004 [ 39 ] M/76 Hypertension Chest pain NA T inversion in I, aVL ST depression in II, III, aVF LAD 90% stenosis, RCA 50% stenosis Korantzopoulos, 2005 [ 40 ] F/73 Hyperlipidemia, Hypertension, Obesity None Elevate ST depression in V2-V5 NA LAD 70% stenosis Cutrer, 2006 [ 5 ] M/53 Hyperlipidemia, Hypertension, Smoking, Obesity None NA NA Negative RCA occlusion, LAD 60% stenosis Morlote, 2006 [ 41 ] F/74 Diabetes, Obesity Chest tightness Evaluate ST depression in V1-V4 NA Not performed F/64 Hyperlipidemia, Hypertension, Diabetes None Not performed Not performed Not performed Not performed Seow, 2007 [ 42 ] M/35 Smoking None Evaluate ST evaluate in V2 to V4 ...…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of this headache is highly variable; it may appear only in concomitance with the acute cardiovascular event [10, 11, 1520] or may be more frequent and even occur daily [4, 5, 9, 21] for periods lasting from a few weeks [5, 9, 12, 13, 2225] to several years [6, 8, 14, 21, 26, 27]. …”
Section: Clinical Featuresmentioning
confidence: 99%
“…Fifty-seven per cent of patients shows pathological alterations of the baseline ECG trace, such as ST-segment elevations or depressions and T-wave inversions [5, 811, 13, 1520, 25, 2729], as well as elevated cardiac enzymes [5, 7, 10, 11, 1620, 26, 27]. …”
Section: Clinical Featuresmentioning
confidence: 99%